Peningkatan Kapasitas Fotografer Pemula Melalui Sekolah Fotografi Online (SeFO) Tingkat Jawa Timur Untuk Mewujudkan Fotografer Mahir dengan Handphone di Masa Pandemik Covid-19 - Amang Fathurrohman; Alfian Adi Saputra; Fauziyah Rahmawati; M. Wildan Adnan; M. Rifqi Nur Habibi (LPPM Universitas Yudharta Pasuruan, 2020)
Condition Pandemic Covid-19 has forced the Indonesian citizen to stay at home. There are no exception for novice photographers who want to add their photography skills. Through e-Comdev, the team carried out a beginner photographer's capacity building assistance through the East Java level of online photography (SeFO) by utilizing WhatsApp social media to parse the problems faced with learning photography during the Covid-19 pandemic. The results of this mentoring show that SeFO participants still have a sense of innovation in improving the capacity of photography. Their skills are also increasingly well-honed in learning the basic photography skills, namely the composition, angle of view, and the explore of the types of photographs. The photo practice they have done is getting better in accordance with the basics of photographic theory. Guided by Tim and the material prepared well is helpful to the participants to understand the material well and feel the benefits of this mentoring more maximally